Investing in German Real Estate: A practical guide - Hackelberg, Florian; Hennig, Dirk (Haufe Lexware, 2021)
Investing in one of the most promising real estate markets in Europe offers enormous opportunities. And as with every real estate market, in Germany too, the local framework conditions must be understood and their particularities must be adequately taken into account. The authors are renowned senior executives, real estate advisors and academics, who share here their extensive experience and real life insights from countless real estate investments, covering all aspects of a successful investment process in Germany. Includes: markets, the regulatory framework and investment guidelines. Contents: Essentials for successful real estate investments in GermanyMacro-economic structure and dynamics of the German real estate marketReal estate investment, trends and strategiesDiverse submarkets: residential, offices, retail, hotel and nursing homesReal estate legal, tax and audit frameworksGerman REITS and ESG in real estate investmentsReal estate M&A, financing, due diligence and valuations